Perspectiva androcêntrica do aborto? Análise sociológica sobre o fenômeno do abortamento entre casais na cidade de João Pessoa - Costa, Mariana Diôgo de Lima (2019)
Women who had come to the maternity under abortion state, and who had arrived unaccompanied, said it was because their partners were not allowed to get into it in the moment of care and hospitalization to the situations of abortion; thus, many men stayed in the gardens of the maternity, trying to follow the process of abortion as they could. The main aim was how the participation of the parent together the women in abortion situation occurs before the prohibition of the male accompaniment in hospitalocentric environment. It was a qualitative exploratory research, through semi-structured interviews with semi-open questions; the study was initiated after previous approval of the Committee of Ethics in Research, as well as after informed consent of the interviewees; it was effected by bibliographic review, ethnography, participant observation and field journal, for analysis of the data we adopted the content analysis approach. Regarding the results, the men and women with the highest educational level were more aware of their rights, self-care with the body, companionship and gender conception, although the majority had had their primary socialization in the traditional molds, based on hegemonic masculinity and a feminization of contraception, abortion, and pregnancy. There was a noticeable discrimination made on the basis of the clothes, clothing, color and schooling of men and women in abortion who present themselves to the maternity ward. It was emphasized the question of the lack of legislation regarding the permission of male accompaniment in the cases of abortion inside the hospital, and the disastrous consequences that this entails; it was discussed the question of gender, mainly how the group of men rethinks their gender identities in the context of postmodernity with new masculinities and femininities, in an attempt to convey the theme of abortion, which is already typically from sociology of health and body, to the sociology of gender that encompasses the masculine gender even in its multiple faces, and it understands the abortion in the masculine sphere sense in subjectivity. It sought to emphasize that the estrangement of the man punishes the woman more in the abortion, going far in a perspective of analyzing the masculinity outside the masculinity hegemonic`s "box", and working for a critical analysis of the masculinity against the present family formations, relationships of couples, and new habits of paternity and maternity. It was also imperative to speak about the bio-power of the State in relation to couples and the public policy of attention to the health of woman and man, feminizing the abortion, pregnancy, and contraception, understanding it as a state violence and reproducing a symbolic violence to the genders that foments empowerment actions. It was seen that the monetary strength is preponderant in the decision to have and not to have a child; in addition to what the decision sometimes passes through who has the purchasing power; when the monetary and labor heads of the family is in the hands of women, increased the precariousness of female labor. The suggested measures are important changes for the formation/ implementation of public policies of health, gender, and juridical to the protection of the paternal accompaniment together women in situation of abortion, as well as the improvement in the service of humanization to abortion.